Association Between Glycemic Control and Hematological Indices in Type 2 Diabetes Mellitus: A Cross-sectional Study - Garg, Nischal; Saini , Tushar Krishnan; Suryavir, Suryavir (Journal of Neonatal Surgery, 2025)
Background: Type 2 diabetes mellitus (T2DM) is a major preventable cause of morbidity due to its chronic complications. Emerging evidence suggests that hyperglycemia affects hematological parameters, which may serve as accessible indicators of disease severity and associated risks. Objective: This study aimed to evaluate the impact of glycemic control on hematological indices among patients with T2DM. Materials and Methods: A cross-sectional study was conducted involving 300 patients with T2DM. Participants were categorized into two groups based on glycemic control: Group A with controlled diabetes (HbA1c <7%) and Group B with uncontrolled diabetes (HbA1c >7%). Data on clinical history, laboratory findings, and hematological parameters were collected and analyzed. Results: Of the 300 patients, 115 (38.3%) had controlled diabetes and 185 (61.7%) had uncontrolled diabetes. Patients with poor glycemic control showed significantly higher levels of total leukocyte count (TLC), monocytes, basophils, red cell distribution width (RDW-CV), platelet distribution width (PDW), mean platelet volume (MPV), platelet large cell ratio (P-LCR), plateletcrit (PCT), neutrophil-to-lymphocyte ratio (NLR), and platelet-to-lymphocyte ratio (PLR) (p < 0.05). Conversely, red blood cell (RBC) count, hemoglobin, mean corpuscular volume (MCV), and mean corpuscular hemoglobin (MCH) were significantly lower in this group (p < 0.05). HbA1c levels showed positive correlations with TLC, neutrophils, basophils, PDW, MPV, PCT, NLR, and PLR, and negative correlations with RBC count, hemoglobin, hematocrit (HCT), and MCV. Conclusion: Poor glycemic control in T2DM is associated with increased inflammatory and prothrombotic markers. Routine hematological indices, being cost-effective and readily available, can serve as useful indicators to assess the severity and complications of diabetes..